The Cash Flow Advantage: Examining Cash Turnover's Moderating Effect on the Profitability Impact of Receivables and Inventory Turnover - Agus Fuadi; Tirin Wulandari; Dini Larasati (LPPM Universitas Pelita Bangsa, 2025)
Efficient working capital management is essential for improving firm profitability, particularly in capital-intensive industries such as pharmaceuticals. This study aims to examine the effects of receivables turnover and inventory turnover on profitability, with cash turnover positioned as a moderating variable. The analysis is conducted on panel data from pharmaceutical companies listed on the Indonesia Stock Exchange during the 2020–2024 period. Panel least squares regression is applied to evaluate both direct and moderating relationships among the variables. The findings show that receivables turnover does not have a significant effect on profitability, whereas inventory turnover has a positive and significant influence. Cash turnover exhibits a limited moderating role in the relationship between both receivables turnover and inventory turnover with profitability. These results indicate that operational efficiency in inventory management plays a more critical role in enhancing profitability than liquidity rotation alone. The study highlights the complexity of financial decision-making in the pharmaceutical sector and provides empirical insights for managers in optimizing working capital strategies.